Global agricultural policy reform and trade : environmental gains and losses - Cooper, Joseph (Cheltenham, UK ; North Hampton, MA, USA : E. Elgar, 2005)
Analyzes the possible linkages between agricultural trade liberalization and the environment, and assesses the negative and positive impacts of any possible reforms. This comprehensive book provides an objective overview of the potential economic consequences of the relationship between trade and the environment. It will be of special interest to agricultural, development and environmental economists as well as policy makers and policy analysts confronting the practical problems of environmental and economic assessment.
Includes bibliographical references (p. 149-164) and index.
oif 27/02/15
Loan
Keywords: Agriculture - environmenal aspects; Agriculture and state; International trade